Risk Factors Analysis of Diabetes Prevalence in Wetland Area: A Study from Borneo Wetland Study on Diabetes - Fajari, Nanang Miftah; Hariyanto, Felix; Nur'amin, Hendra; Hasrianti, Nuvita (Universitas Brawijaya, 2024)
Background: National Basic Health Survey held by the Ministry of Health Republic of Indonesia shows the prevalence of Diabetes Mellitus increased from 6.9% to 8.5% in 2018. Wetland is an area covered by shallow water on the surface, which represents a unique ecosystem. Aim: This study investigated the association between various risk factors and DM prevalence in South Kalimantan Wetlands, Indonesia. Early identification and management of risk factors may prevent progression into diabetes mellitus. Methods: We conducted the Borneo Wetland Study on Diabetes (Best-Diab 1) with a cross-sectional study approach using the latest health survey data conducted by the South Kalimantan Provincial Health Office from the primary health center visit from January 2020 to March 2022. Using Proportionate Random Sampling, we divided samples into two groups; 6.010 in the DM group, and 6.010 non DM group. Results: Gender, age, BMI, blood pressure, and blood glucose level were significantly correlated with diabetes mellitus prevalence (p<0.001). Family history of DM surprisingly has a significant impact on DM prevalence (PR, 3.16; 95% CI, 2.80-3.57, p<0.001). The prevalence of DM in the smoking group was 0.78 times less than in non-smoking individuals (PR, 0.78; 95% CI, 0.74-0.82; p<0.001). Excess sugar was the greatest risk factor for diabetes mellitus, with the prevalence of DM 4.72 times greater than normal sugar intake (PR, 4.72; 95% CI, 4.29-5.2; p<0.001). Excess salt intake also seemed to be a significant risk factor among DM patients (PR, 1.24; 95% CI, 1.17-1.30, p<0.001. Conclusion: Females, older age, higher BMI, and family history of DM were significant risk factors for diabetes mellitus prevalence in this study. Further studies are needed to determine how those factors impacted diabetes mellitus. Keywords: risk factors, prevalence, diabetes mellitus, wetland, South Kalimantan